Cyclin D Degradation by E3 Ligases in Cancer Progression and Treatment - Qie, Shuo (Semin Cancer Biol, 2020)
D cyclins include three isoforms: D1, D2, and D3. D cyclins heterodimerize with cyclin-dependent kinase 4/6 (CDK4/6) to form kinase complexes that can phosphorylate and inactivate Rb. Inactivation of Rb triggers the activation of E2F transcription factors, which in turn regulate expression of genes whose products drive cell cycle progression. Because D-type cyclins function as mitogenic sensors that link growth factor signaling directly with G(1) phase progression, it is not surprising that D cyclin accumulation is dysregulated in a variety of human tumors. Elevated expression of D cyclins results from gene amplification, increased gene transcription and protein translation, decreased microRNA levels, and inefficiency or loss of ubiquitylation-mediated protein degradation. This review focuses on the clinicopathological importance of D cyclins, how dysregulation of Ubiquitin-Proteasome System (UPS) contributes to the overexpression of D cyclins, and the therapeutic potential through targeting D cyclin-related machinery in human tumors.